Między nonkonformizmem a kolaboracją. Kontakty polsko-niemieckie w biografii Jana Emila Skiwskiego - Polechoński, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
In the interwar period, Jan Emil Skiwski gained recognition as an outstanding literary critic. While the Nazis occupied Poland during World War II, as one of the few writers with ideological motives, he collaborated with the Germans, supporting their propaganda activities, including in the magazine “Przełom”. His attitude was met with general condemnation. After the war, the writer chose to emigrate, hiding behind a changed name, especially given that in communist Poland, he was sentenced in absentia to life imprisonment and loss of public rights. An interesting episode in his post-war biography is the friendship he developed with the German intellectual Jürgen Rausch during his stay in the Allied camp for prisoners of war in Italy. The article tries to present these special Polish–German relations of Skiwski.